New Techniques of Image Denoising using Multiwavelet by Neighbor Mapping (Journal of the College of Basic Education, 2023)
The Image denoising naturally corrupted by noise is a classical problem in the field of signal or image processing. Denoising of a natural images corrupted by Gaussian noise using multi-wavelet techniques are very effective because of its ability to capture the energy of a signal in few energy transfer values. Multi-wavelet can satisfy with symmetry and asymmetry which are very important characteristics in signal processing. The better denoising result depends on the degree of the noise. Generally, its energy is distributed over low frequency band while both its noise and details are distributed over high frequency band. Corresponding hard threshold used in different scale high frequency sub-bands. In this paper proposed to indicate the suitability of different wavelet and multi-wavelet based and a size of different neighborhood on the performance of image Denoising algorithm in terms of PSNR value. Finally it's compare wavelet and multi-wavelet techniques and produced best denoised image using neighbor mapping and multiwavelet technique based on the performance of image denoising algorithm in terms of PSNR Values.